A review of the Mutillidae (Hymenoptera) of Yemen - Lelej, Arkady S.; van Harten, Antonius (Zootaxa, 2006)
Forty species in 19 genera are recorded from Yemen. Three new genera are described: Paglianotilla gen. nov. (type species P. hogenesi sp. nov.), Rasnitsynitilla gen. nov. (type species R. brachyptera sp. nov.), and Vanhartenidia gen. nov. (type species V. felix sp. nov.). Ten new species are described: Arnoldtilla achterbergi sp. nov. (Yemen), Dentilla ehrenbergi sp. nov. (Yemen, Saudi Arabia), P. hogenesi sp. nov. (Yemen), R. brachyptera sp. nov. (Yemen), R. invreai sp. nov. (Yemen), R. schmideggeri sp. nov. (Yemen), V. arabica sp. nov. (Yemen), V. felix sp. nov. (Yemen), V. tihama sp. nov. (Yemen), and Spinulomutilla yemenita sp. nov. (Yemen). Hitherto unknown females are recognized for Arnoldtilla Nonveiller, Omotilla Invrea, and Tropidotilla milmili (Magretti). New synonymy is proposed for Omotilla Invrea 1943 = Conjunctotilla Nonveiller 1996, syn. nov.; Pseudophotopsis aurea (Klug 1829) = Mutilla kassalina Magretti 1898, syn. nov., P. continua arabica Hammer 1962, syn. nov. New status is proposed for Arnoldtilla Nonveiller, Myrmilla rubida Magretti, M. parvula Magretti, Glossotilla djiboutiensis Bischoff, V. kassalana (Bischoff), V. pyrrhospilota (Bischoff). New combination is proposed for: A. bischoffi (Arnold), A. silvestris (Arnold), O. conjuncta (Klug), O. conjunctoides (Magretti), O. grazianii (Invrea), Dentilla arabica (Hammer), V. dives (Smith), V. kassalana (Bischoff), V. pyrrhospilota (Bischoff), V. tricolor (Klug), and V. unguiculata (Magretti). Eleven genera are recorded for the first time from Yemen: Arnoldtilla Nonveiller, Omotilla Invrea, Macromyrme Lelej, Ronisia Costa, Strangulotilla Nonveiller, Tropidotilla Bischoff, Dentilla Lelej, Glossotilla Bischoff, Dentotilla Nonveiller, Spinulomutilla Nonveiller, and Dasylabris Radoszkowski. Seventeen species are recorded for the first time from Yemen: Pseudophotopsis maura Bischoff, P. mascatiana Invrea, Myrmilla parvula Magretti, M. rubida Magretti, T. bellii (Magretti), T. carinulifera Bischoff, T. frontalis (Klug), T. milmili (Magretti), Strangulotilla samharica (Magretti), Ronisia idonea (André), Dentilla testacea (Klug), Glossotilla djiboutiensis Bischoff, Dentotilla auricoma (Bischoff), Dasylabris biblica Invrea, Tricholabiodes niloticus Suárez, T. pedunculatoides Bischoff, and T. sudanensis Suárez. Dentilla testacea (Klug) and Tricholabiodes chloroticus (Gribodo) are recorded for the first time from Saudi Arabia. Tricholabiodes sudanensis Suárez is recorded for the first time from Oman. Glossotilla djiboutiensis Bischoff is recorded for the first time from Eritrea. Keys to eight species of Vanhartenidia and three species of Rasnitsynitilla are given.